2021
DOI: 10.1039/d1py00647a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of ethylene–norbornene–1-octene terpolymers with high 1-octene contents, molar masses, and tunable Tg values, in high yields using half-titanocene catalysts

Abstract: Terpolymerizations of ethylene (E) and norbornene (N) with 1-octene (O) using different aryloxo- or ketimide-modified half-titanocene catalysts, Cp’TiCl2(O-2,6-iPr2C6H3) [Cp’ = indenyl (1), C5Me5 (Cp*, 2), tBuC5H4 (3)] and Cp’TiCl2(N=CtBu2) [Cp’...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…10 in Table 2). Boggioni et al [ 93 ] used ketimide‐modified CpTiCl 2 (N=C t Bu 2 ) (Figure 11C) to catalyze the terpolymerization of ethylene, norbornene, and 1‐octene at 60°C. The maximum activity of the catalyst was 9.77 × 10 7 g polymer/(mol h), and the 1‐octene insertion amount was 5.6 mol%.…”
Section: Metallocene Catalyst For Ethylene/α‐olefin Solution Copolyme...mentioning
confidence: 99%
See 1 more Smart Citation
“…10 in Table 2). Boggioni et al [ 93 ] used ketimide‐modified CpTiCl 2 (N=C t Bu 2 ) (Figure 11C) to catalyze the terpolymerization of ethylene, norbornene, and 1‐octene at 60°C. The maximum activity of the catalyst was 9.77 × 10 7 g polymer/(mol h), and the 1‐octene insertion amount was 5.6 mol%.…”
Section: Metallocene Catalyst For Ethylene/α‐olefin Solution Copolyme...mentioning
confidence: 99%
“…Since then, Nomura et al [88][89][90][91][92]94] have done a lot of in-depth research on such catalysts from the crystal structure and catalytic mechanism to the ligand structure of the catalyst and the effect of the comonomer on the polymerization effect. Studies have found that such catalysts were suitable for not only the polymerization of ethylene but also the copolymerization of ethylene with monomers such as α-olefins, [88][89][90] substituted α-olefins, [91,92] cyclic olefins, [93] and silane olefins. [94] Kim et al [95] found that phenyl-substituted aryloxy semi-titanocenes Cp*Ti(O-2-PhC 6 H 4 )Cl 2 (Figure 11B) had higher activity than [Me 2 Si (C 5 Me 4 )(N t Bu)]TiCl 2 for ethylene/1-octene copolymerization at 140 C and also had better insertion ability of comonomers (see No.…”
Section: Half-metallocene Catalystsmentioning
confidence: 99%
“…In contrast to the ethylene (E)/cyclic olefin copolymers, reports for the synthesis of propylene (P) or α-olefin copolymers still have been limited to NBE [poly­(P- co -NBE)­s, poly­(α-olefin- co -NBE)­s], or the terpolymers (with styrene and 1-hexene). We previously reported the synthesis of α-olefin copolymers with NBE and TCD (α-olefin = 1-hexene, 1-octene, and 1-dodecene) and demonstrated linear relationships between T g values and the NBE or CD contents; as described above, the T g values in poly­(α-olefin- co -TCD)­s were higher than those in poly­(α-olefin- co -NBE)­s with the same cyclic olefin contents . However, there were no reports for the synthesis of other amorphous propylene cyclic copolymers including the effect of the cyclic structure on the thermal property ( T g ) as well as a comparison with the ethylene copolymers.…”
Section: Introductionmentioning
confidence: 99%
“…1–4 Both early and late transition metal complexes have been reported as active catalysts for the vinyl addition polymerization of NB. 1,5–11 Recently, promising catalytic activities have also been reported for late transition metal catalysts, such as Pd- and Ni-based catalysts. 12–15…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Both early and late transition metal complexes have been reported as active catalysts for the vinyl addition polymerization of NB. 1,[5][6][7][8][9][10][11] Recently, promising catalytic activities have also been reported for late transition metal catalysts, such as Pd-and Ni-based catalysts. [12][13][14][15] The choice of ancillary ligand signicantly affects the catalytic performance of the metal-based initiators in a polymerization reaction.…”
Section: Introductionmentioning
confidence: 99%